ALGORITHM FOR CONSTRUCTING TRIPLE IDENTITY GRAPH OF RING Z_n USING PYTHON - Kurniawan, Vika Yugi; Ekasiwi, Chessa Fanny (PATTIMURA UNIVERSITY, 2024)
Let R be a commutative ring. The triple identity graph of ring R is denoted by TE(R) with sets of vertices Two different vertices and are adjacent if and only if there is an element in such that and . To easily visualize the triple identity graph, a program is needed to represent it briefly. Python can easily manipulate, analyze, and visualize data. Therefore, this study uses Python to construct the algorithm for In this research, some examples will be given and then be observed for new characteristics of the triple identity graph of ring such as the connectedness, the diameter, and the girth. And we find the characterize for which graph is empty, connected, or Hamiltonian.